The nucleus reuniens: a key node in the neurocircuitry of stress and depression. - Kafetzopoulos, V; Kokras, N; Sotiropoulos, I; Oliveira, J F; Leite-Almeida, H; Vasalou, A; Sardinha, V M; Papadopoulou-Daifoti, Z.; Almeida, O F X; Antoniou, K; Sousa, N.; Dalla, C (Mol Psychiatry, 2018)
The hippocampus and prefrontal cortex (PFC) are connected in a reciprocal manner: whereas the hippocampus projects directly to the PFC, a polysynaptic pathway that passes through the nucleus reuniens (RE) of the thalamus relays inputs from the PFC to the hippocampus. The present study demonstrates that lesioning and/or inactivation of the RE reduces coherence in the PFC-hippocampal pathway, provokes an antidepressant-like behavioral response in the forced swim test and prevents, but does not ameliorate, anhedonia in the chronic mild stress (CMS) model of depression. Additionally, RE lesioning before CMS abrogates the well-known neuromorphological and endocrine correlates of CMS. In summary, this work highlights the importance of the reciprocal connectivity between the hippocampus and PFC in the establishment of stress-induced brain pathology and suggests a role for the RE in promoting resilience to depressive illness.
Keywords: Animals; Antidepressive Agents; Depression; Depressive Disorder; Hippocampus; Male; Midline Thalamic Nuclei; Neural Pathways; Prefrontal Cortex; Rats; Stress, Psychological